Aktualisasi Checks And Balances Lembaga Negara: Antara Majelis Permusyawaratan Rakyat dan Mahkamah Konstitusi - Hanif Fudin (The Constitutional Court of the Republic of Indonesia, 2022)
The 1945 Constitution as the constitution of the Indonesian state which adopts a distribution of power system accompanied by a mechanism of checks and balances between state institutions based on popular sovereignty. In this case, as the People's Consultative Assembly and the Constitutional Court which have the authority related to the 1945 Constitution directly. Then it contains the research distinction that is the actual inherence of the authority of the People's Consultative Assembly and the Constitutional Court institutions as the guardians of the constitution through a technical review of checks and balances. Therefore, to scientifically strengthen this legal research, a juridical-normative, philosophical and conceptual-critical approach is used. On that basis, it is considered that between the People's Consultative Assembly and the Constitutional Court have actual significance of the checks and balances mechanism on their institutional authority as the guardian of the constitution. Therefore, it has implications for strengthening the institutional authority of the said state institution and realizing the order of legal civilization and democracy in the 1945 Constitution as the state constitution which is the central point of the administration of the Indonesian state as a democratic law state.